Peace and Reconciliation In Search of Shared Identity. - Kim, Sebastian C. H.; Kollontai, Pauline; Hoyland, Greg. (Farnham : Ashgate Pub., 2008)
Establishing a shared identity is an important part of any process of peace and reconciliation. This book discusses issues and theories of identity formation that can be implemented for peace and reconciliation from the perspectives of theology and religious studies, whilst interacting with politics, socio-cultural studies and economics. By focusing on the theme of peace and reconciliation, and employing an interdisciplinary approach, this volume will make a significant contribution to the discussion of the situation of the Korean peninsula, and wider global contexts. The volume explores theor.
7 Towards Reconciliation and Justice in South Africa: Can Church Unity Make a Difference?8 Korean War: The Origin of the Axis of Evil in the Korean Peninsula; 9 Towards Peace and Reconciliation between South and North Korean Churches: Contextual Analysis of the Two Churches; 10 Strategies for Peace and Reunification in Korea; 11 Reconciliation Possible? The Churches' Efforts Toward the Peace and Reunification of North and South Korea; Appendix 1: July.
Print version record.
Master record variable field(s) change: 072
Keywords: Identification (Religion); Peace -- Religious aspects; Reconciliation -- Religious aspects; Peace; Identification (Religion); Peace -- Religious aspects; Reconciliation -- Religious aspects; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; RELIGION / Christian Life / Social Issues; Electronic books